1982
DOI: 10.1136/vr.110.6.121
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation of hypothermic lambs

Abstract: A technique was developed for the resuscitation of hypothermic newborn lambs. This technique consisted of three major components: the administration of glucose solution by intraperitoneal injection to lambs aged six hours or more in order to reverse hypoglycaemia (10 ml/kg of a 20 per cent solution); rewarming the lambs in air at 40 degrees C; and careful attention to the nutrition and husbandry of the lambs after rewarming. The results indicate that careful application of this technique during lambing would c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Careful observation and foster mothering of weak and abandoned lambs at birth, including artificial warming during cold periods of the year to prevent SME and reduce neonatal mortality (Eales et al, 1982). Young lambs should not be allowed to graze hard, fibrous dry grass, so as to avoid the formation of bezoars in the abomasum.…”
Section: Discussionmentioning
confidence: 99%
“…Careful observation and foster mothering of weak and abandoned lambs at birth, including artificial warming during cold periods of the year to prevent SME and reduce neonatal mortality (Eales et al, 1982). Young lambs should not be allowed to graze hard, fibrous dry grass, so as to avoid the formation of bezoars in the abomasum.…”
Section: Discussionmentioning
confidence: 99%
“…Once rewarmed the lambs quickly regained normal activity and exhibited a strong suckling drive. In a rewarming study reported by Eales et al (1982b), 16 of 89 hypothermic lambs died during resuscitation in a 40'C air environment. The lambs used in the studies of Eales et al (1982a,b) were found in the held in a hypothermic state of unknown durations prior to the attempted resuscitations and therefore the results are not directly comparable with the present study.…”
Section: Induction Of Hypothermia and Test Proceduresmentioning
confidence: 99%
“…Trois m6thodes ont servi au r6chauffement des sujets: (A) immersion dans de I'eau chaude (38'C); (B) (Martin et al 1975l. Slee 1977Haresign etal.1977;Eales et al 1982b Bennen 1982) and has been reported to decline in newborn lambs (Alexander 1962) (Robinson et al 1986). However, the extent of hypothermia in these lambs was substantially less than the, on average, 30'C identified by shepherds with field animals (Eales et al 1982a).…”
mentioning
confidence: 99%
“…First, the availability of carbohydrate and not lipid is the ultimate determinant of the period during which a new-born's well being will not be threatened. Even and the resulting hypoglycaemia lead to depressed heat production which causes hypothermia and to compromised cerebral function, indicated by coma, convulsions and other symptoms (Goodwin, 1957;McCance & Widdowson, 1959;Alexander, 1962c;Cormblath & Schwartz, 1966;Shelley & Neligan, 1966;Eales, Small & Armstrong, 1980;Eales, Gilmour, Barlow & Small, 1982a;Eales, Small & Gilmour, 1982c). Hypothermia usually precedes cerebral compromise and is often the cause ofdeath in cold conditions, whereas cerebral compromise usually causes death in thermoneutral conditions.…”
Section: Utilization Of Body Energy Reservesmentioning
confidence: 99%